The social and political role of women in the Sassanid state (224-651 AD) - Amin, Prof.Dr.Narmin Ali Mohammed; Abdulwahid, Asst.Prof.Dr. Kulthumah Jameel (Sulaimani Journal for Humanities, 2026)
The Sassanid state was based on religion (Zoroastrianism), both political and religious power was under the direction of religious men, thus the social and political position of women was according to the Avesta Raising a capable generation so that they can fight against the enemies of truth and purity, and in the future become useful members to serve society and the state, so much emphasis was placed on family formation and marriage. During these ten years, nine kings came to power, two of whom were women. Due to the dominance of terrorism in the palace and the poor political situation, the throne was given to two daughters. 590-628 AD) (Boran Dokht and Azermidokht) deserted, in general, with comments on the situation of women in the Sassanid state, but compared to neighboring countries had the right to economic independence and choice of marriage.
Keywords: Sassanid state; Avesta; family; education; political situation; Buran Dokht; Azermidokht